Case report: Structural brain abnormalities in TUBA1A-tubulinopathies: a narrative review - Pavone, Piero; Striano, Pasquale; Cacciaguerra, Giovanni; Marino, Simona Domenica; Parano, Enrico; Pappalardo, Xena Giada; Falsaperla, Raffaele; Ruggieri, Martino (Frontiers in Pediatrics, 2023)
Introduction: Tubulin genes have been related to severe neurological complications and the term 'tubulinopathy' now refers to a heterogeneous group of disorders involving a wide family of tubulin genes with TUBA1A being the most common. A review was carried out on the complex and severe brain abnormalities associated with this genetic anomaly. Methods: A literature review of the cases of TUBA1A-tubulopathy was performed to investigate the possible link of the molecular findings with cerebral anomalies and to describe the clinical and neuroradiological features related to this genetic disorder. Results: Clinical manifestations of TUBA1Atubulinopathy patients are heterogeneous and severe ranging from craniofacial dysmorphism, notable developmental delay, and intellectual delay to early onset seizures, neuroradiologically associated with complex abnormalities. TUBA1A-Tubulinopathy may be display different various and complex cortical and subcortical malformations. Discussion: A range of clinical manifestations related to different cerebral structures involved may be observed in patients with TUBA1A-tubulinopathy. Genotype-phenotype correlations are here discussed. Individuals with cortical and subcortical anomalies should be screened also for pathogenic variants in TUBA1A.Introduction: Tubulin genes have been related to severe neurological complications and the term 'tubulinopathy now refers to a heterogeneous group of disorders involving a wide family of tubulin genes with TUBA1A being the most common. A review was caried out on complex brain abnormalities and on DWM phenotype associated to this genetic disorder.